Designing Augmented Reality-based Tele-Education Management Systems: Improving Access and Interactivity in Remote Learning - Tarigan, Herlina (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2024)
Integrating Augmented Reality (AR) in Tele-Education Management Systems (TEMS) enhances student engagement and interactivity in remote learning. Traditional methods often lack active participation, reducing learning outcomes. This research examines how AR-based TEMS improves interaction, understanding, and retention, especially in STEM education. A qualitative approach using secondary data from peer-reviewed studies, governmental reports, and educational case studies identified AR adoption trends. Findings highlight AR's ability to deliver immersive, interactive learning experiences that surpass traditional methods. However, barriers such as limited internet bandwidth, access to advanced hardware, and inadequate technical support challenge adoption in underserved areas. Solutions include optimizing AR for low-bandwidth environments and providing affordable, mobile-compatible devices. Additionally, AR enhances comprehension and retention of complex concepts, positioning it as a transformative tool for remote education by making learning more interactive, accessible, and effective.